2014
DOI: 10.1007/s12253-014-9847-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostıc Value of Increased her2 Expression in Cancers of Pancreas and Biliary Tree

Abstract: Increased HER2 expression has a prognostic, and predictive value in many solid cancer types, predominantly in breast cancer. However the effects of HER2 on survival from cancers of pancreas, gall bladder, cholangiocellular, and ampullary region are not known. In this study, the effects of increased HER2 expression on these types of cancer have been analyzed. Immunohistochemical HER2 staining was performed in 31 (44.9 %) female, and 38 (55.1 %) male patients with a mean age of 65 ± 10 years, and various paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…For this reason, molecular characterization is becoming crucial for the identification of potential therapeutic targets and more accurate patient stratification beyond conventional clinicopathological features. Previous studies described the incidence of HER2 alterations in different cohorts of BTC, but the clinical implication of such alteration has not been clarified [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, molecular characterization is becoming crucial for the identification of potential therapeutic targets and more accurate patient stratification beyond conventional clinicopathological features. Previous studies described the incidence of HER2 alterations in different cohorts of BTC, but the clinical implication of such alteration has not been clarified [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The reported rates of HER2 overexpression in pancreatic cancer, defined as 3+ in immunohistochemical staining or gene amplification by in situ hybridization (ISH), vary from 0%-11% [ 16 23 ]. Similarly to other tumour types, high expression of HER2 in pancreatic cancer has been associated with a shorter survival [ 24 ], but other studies have found the opposite [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In tumours of the ampulla, distal bile duct and gall bladder, the frequency of HER2 overexpression has been low, and comparable to pancreatic cancer in a few small studies [ 16 , 17 , 23 ], whereas larger studies have found overexpression in 6–13% of ampullary tumours [ 27 , 28 ], and 23% and 17% of tumours of the bile duct and gall bladder [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of this heterodimer is advantageous over heterodimers that are formed by other members in EGFR family, causing a cascade reaction. 19,20 HER2 protein and ligand participate in physiological activities of cells to facilitate their activation, proliferation, and differentiation. 21 The occurrence, development, and invasion or metastasis of tumors is correlated with HER2 overexpression.…”
Section: Discussionmentioning
confidence: 99%